Comparing the effectiveness of robot-based to human-based intervention in improving joint attention in autistic children - So, Wing-Chee; Law, Wing-Wun; Cheng, Chun-Ho; Lee, Cassandra; Ng, Ka-Ching; Kwok, Fai-Yeung; Lam, Ho-Wai; Lam, Ka-Yee (Frontiers in Psychiatry, 2023)
Background: Children with autism have impairments in initiation of joint attention (IJA) and response to joint attention (RJA). Aims: The present study compared the learning effectiveness of robot-based intervention (RBI) with that of content-matched human-based intervention (HBI) in improving joint attention (JA). We examined whether RBI would enhance RJA, in comparison to HBI. We also examined whether RBI would increase IJA, in comparison to HBI. Methods and Procedures: Thirty-eight Chinese-speaking children with autism aged 6 to 9 years were randomly assigned to RBI and HBI groups. Before intervention, their autism severity, cognitive abilities, and language skills were assessed. Each child received six 30-minute training sessions over three weeks. During training, he/she watched one or two robot/human dramas twice where two robot/human actors demonstrated eye contact and RJA. Outcomes and Results: Children in the RBI (but not HBI) group produced more RJA and IJA behaviors in the delayed post-test than in the pre-test. Parents of the RBI children rated the program more positively than those of the HBI children. Conclusions and Implications: RBI may be more effective than HBI in promoting JA in autistic children with high support needs. Our findings shed light on the application of robot dramas in enhancing social communication skills.